Soil Macrofauna as Bioindicator on Aek Loba Palm Oil Plantation Land - Arlen Hanel Jhon; Abdul Rauf; T Sabrina; Erwin Nyak Akoeb (Program Pascasarjana Universitas Sriwijaya, 2020)
Oil palm plantations of PT. Socfin Indonesia (Socfindo) Aek Loba area has been planted with oil palm since 1931, currently has plants from generation I (± 31 years), II (± 47 years), III (± 74 years), and IV (± 86 years) . The difference in the length of time of utilization and management of plantation land in each generation also determines the presence, both species, density, relative density, and the frequency of the presence of soil macrofauna. Soil macrofauna plays a role in maintaining the balance of the soil ecosystem. This research has been conducted at PT. Socfindo Kebun Aek Loba in February 2017- April 2018. This research was conducted to determine the presence of soil macrofauna on oil palm plantation land of PT. Socfin Indonesia (Socfindo) Aek Loba plantation area. Determination of the sampling point is done by the Purposive Random Sampling method, soil macrofauna sampling using the Quadratic and Hand Sorting methods. There are 29 species of soil macrofauna which are grouped into 2 phyla, 3 classes, 11 orders, 21 families, and 27 genera. The highest density value is in the Generation II area of 401.53 ind / m2 and the lowest density value is in the Generation IV area of 101.59 ind / m2. Frequency The presence of soil macrofauna in the four generations consists of 4 species, namely Pontoscolex corethrurus, Geophilus flavus, Vostax apicedentatus, and Solenopsis fugax.